2018
DOI: 10.2174/1573406413666171129224424
|View full text |Cite
|
Sign up to set email alerts
|

Prodrugs for Nitroreductase Based Cancer Therapy- 1: Metabolite Profile, Cell Cytotoxicity and Molecular Modeling Interactions of Nitro Benzamides with Ssap-NtrB

Abstract: Amongst all metabolites of prodrugs after Ssap-NtrB reduction, N-(2,4- dinitrophenyl)-4-nitrobenzamide (3) was efficient and toxic in PC3 cells as comparable as CB1954. Kinetic parameters, molecular docking and HPLC results also confirm that prodrug 3 is better for Ssap-NtrB than 1, 2 and 4 or known cancer prodrugs of CB1954 and SN23862, demonstrating that prodrug 3 is an efficient candidate for NTR based cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…75 Molecular modeling studies may furthermore allow optimization of the prodrug for the NTR system, and cell viability studies with a series of nitro-substituted benzamide prodrugs have led to the discovery of novel prodrug candidates with promising kinetic and molecular docking profiles for NTR-based therapy. 76 Other PAGT approaches/systems…”
Section: Ntr Systemsmentioning
confidence: 99%
“…75 Molecular modeling studies may furthermore allow optimization of the prodrug for the NTR system, and cell viability studies with a series of nitro-substituted benzamide prodrugs have led to the discovery of novel prodrug candidates with promising kinetic and molecular docking profiles for NTR-based therapy. 76 Other PAGT approaches/systems…”
Section: Ntr Systemsmentioning
confidence: 99%
“…Prodrug strategies based on NTR have been extensively studied and a library of different nitro-containing prodrugs has led to promising in vitro prodrug candidates [21]. In addition, the design and synthesis of nitro containing compounds as diagnosis of tumor cells have come to the fore in recent years [22][23][24][25][26], some nitro benzamides have special attention as anti-tumor agents due to their remarkable effects obtained from in vitro/in vivo studies and also from clinical trials during treatment of some cancers [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these prodrugs have been determined as effective candidates in PC3, Hep3B, and HT29 cancer cell lines and in HUVEC normal healthy cell line. [26][27][28][29] Computational approaches such as molecular docking and MD simulation studies have been widely used an important tool for discovery and design of drug candidates and are highly useful for understanding the interactions between ligand and protein. [30][31][32] The latest studies have shown that computational assessments with combined in vitro studies contribute to further studies such as in vivo and clinical translation.…”
Section: Introductionmentioning
confidence: 99%